Lyme disease in UK primary care: a knowledge, attitude, and practice survey - Lucy Delaney; Amanda Semper; Neil French; John SP Tulloch (BJGP Open)
Background: Lyme disease (LD) cases in the UK most commonly present within the primary care setting. Despite an upward trend of incidence, little is known regarding GP experience with diagnosis and treatment. Aim: This study aims to describe baseline primary care clinician Knowledge, Attitude and Practice (KAP) in Scotland and England. Design & setting: Online KAP survey on LD for UK-based practising GPs. Method: An online KAP questionnaire was developed for use in UK primary care. The survey was distributed through UK-based research networks, professional societies, and via social media. Results: A total of 191 complete responses were analysed (England n = 130, Scotland n = 61). The Scotland-based responder group had more relevant consultations in the previous 3 years. Responders from Scotland demonstrated a greater awareness that erythema migrans (EM) is pathognomonic for LD and that serological testing of this patient group is not indicated. Less common cardiac and neurological symptoms were not as well associated with LD by both responder groups for the former and England-based responders for the latter. Prescribing according to the National institute for Health and Care Excellence (NICE) guidance was identified in 70% of Scotland and 42% of England-based GP responses. Conclusion: Targeted resources may improve clinician confidence on exposure risk, symptom recognition, testing limitations and treatment dose and duration. Scotland-based responders’ better survey performance potentially reflects greater clinical exposure and public awareness of the disease, due to high endemicity within the nation.